Complementary and alternative medicine in the management of hypertension in an urban Nigerian community (2010)
Hypertension is a common non communicable condition worldwide. In developing countries (including Nigeria), the use of complementary and alternative medicine (CAM) is common. This study investigated the frequency and factors associated with use of CAM among hypertensive subjects in an urban Nigerian community. Perspectives about the management of hypertension were obtained from CAM practitioners in the community. Methods: Four hundred and forty hypertensive subjects in Idikan community, Ibadan, were interviewed using a semi-structured survey instrument. Association between categorical variables was tested using the chi-square test. Logistic regression analysis was done to identify independent predictor variables of CAM use, with CAM use as the outcome variable and the demographic and belief items as predictor variables. In-depth interviews were conducted with all known CAM practitioners in the community on issues relating to their beliefs, knowledge, practice and experiences in managing patients with hypertension in the community. Results: In the study sample, 29% used CAM in the management of their hypertension. Among those using CAM, the most common forms used were herbs (63%) and garlic (21%). Logistic regression analysis revealed that four variables were independent predictors of CAM use: being male (OR 2.58, p < 0.0001), belief in supernatural causes of hypertension (OR 2.11, p = 0.012), lack of belief that hypertension is preventable (OR 0.57, p = 0.014) and having a family history of hypertension (OR1.78, p = 0.042). Other factors such as age, educational level and occupation were not independent predictors of CAM use. Interviews with CAM practitioners revealed that they believed hypertension was caused by evil forces, stress or "too much blood in the body". They also thought they could cure hypertension but that reduced costs (compared to hospitals) was one of the reasons most of their clients consult them. Conclusions: The use of CAM is common among hypertensive subjects in this urban Nigerian community. Men were more than twice as likely to use CAM and belief in supernatural causes of hypertension was the most notable belief predicting CAM use. Interviews with CAM practitioners yielded useful perspectives about the role they play in hypertension management in the community. This study adds to the small but growing literature about the use of CAM in hypertension in sub Saharan Africa. Further studies in hypertension and other non communicable disease are needed.